2012
DOI: 10.1371/journal.pone.0041412
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Apoptosis Act as Partners to Induce Germ Cell Death after Heat Stress in Mice

Abstract: Testicular heating suppresses spermatogenesis which is marked by germ cell loss via apoptotic pathways. Recently, it is reported that autophagy also can be induced by heat treatment in somatic cells. In this study, the status of autophagy in germ cells after heat treatment, as well as the partnership between autophagy and apoptosis in these cells was investigated. The results demonstrated that besides initiating apoptotic pathways, heat also induced autophagic pathways in germ cells. Exposure of germ cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(156 citation statements)
references
References 42 publications
12
138
1
Order By: Relevance
“…In stallion spermatozoa, STF-62247 and rapamycin induced a significant decrease in viability, whereas chloroquine and 3-MA had no effect on this parameter. Our results are in accordance with those published by Zhang et al (2012), where autophagy-induced germ cell death after heat stress in mice.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In stallion spermatozoa, STF-62247 and rapamycin induced a significant decrease in viability, whereas chloroquine and 3-MA had no effect on this parameter. Our results are in accordance with those published by Zhang et al (2012), where autophagy-induced germ cell death after heat stress in mice.…”
Section: Discussionsupporting
confidence: 94%
“…LC3 protein is processed under stress in sperm Zhang et al, 2012). Therefore, our next objective was to investigate whether autophagy was activated as a survival mechanism or, in opposition, was induced to produce cell death.…”
Section: Discussionmentioning
confidence: 99%
“…81 Later, by utilizing different cellular techniques and models, it was shown that heat stress, as high as 43 C, induces autophagy. 82 Heat exposure also triggers autophagy in a human hepatoma cell line, 83 rat cardiomyocytes, 84 human alveolar basal epithelial cells, 5 a mouse spermatocyte cell line, 85 and human cervical cancer cells. 86 Moreover, recent studies have shown that deletion of the heat shock transcription factor 1 (HSF1), increases basal autophagy levels.…”
Section: A Correspondence Between Immune and Muscle Cellsmentioning
confidence: 99%
“…Autophagy and apoptosis together induce cell death [30] and enhance radiosensitivity [31] . Apoptosis can also be induced via enhanced autophagy [32] .…”
Section: Induction Of Gsc Apoptosis By Co-treatment With Ir and Nvp-bmentioning
confidence: 99%